The impact of CEFTA on exports, economic growth and development - Victoria Pistikou (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2020)
Purpose: The aim of the paper is to evaluate the impact of CEFTA on exports and economic growth and development of its members. Regionalism is attractive to states and especially to developing countries, since they enhance their reliability on reforms to foreign investors and they raise their bargaining power in multilateral level, since they negotiate as a unit and not individually, especially within the WTO, achieving goals which would not had been achieved if they had acted individually. The paper is based on the theoretical context of Regional Trade Agreements. More specifically, Free Trade Agreements widens trade in goods and services, raises exports and increases distribution of production. Moreover, FTAs affect state's reliability for inward investments, since they guarantee the implementation of domestic reforms. In particular, compared to WTO, within an FTA less countries are involved therefore, it is easier for them to monitor a state and if this state deviates from its commitments then it will face direct retaliation from other regional partners. Consequently, its members are considered more reliable and they experience a boost in economic growth and volume of trade. Design/methodology/approach: Methodologically it is based on analyzing quantitative macroeconomic data and qualitative data that have been quantified through a comparative analysis among members states. More specifically, the analytical framework consists of additional variables concerning economic and political freedom as well as trade volume, growth, development and income, since that all are correlated with trade liberalization. Findings: In the case of CEFTA, intra-regional trade seems to be neglected since all CEFTA members prefer trading with the EU. This does not mean that CEFTA's economies could be more competitive than the EU, however, there are is no increase in intra-regional trade volume and when there is, this concerns only few of the partners. In addition, indexes show that economic environment remains protected and state centric. The fact that an FTA such as CEFTA seems that does not have any impact on GDP growth but at the same time GDP per capita and HDI are increasing, might show that there are other variables which affect these indexes. another paradox is that these positive developments happen in highly corrupted, state-centric and protectionist members of a Free Trade Agreement. Research limitations/implications: FDI were not examined due to lack of data. Originality/value: Up to now, there are contradictory arguments in the literature regarding the effects of CEFTA on its members. More particularly, there are scholars who argue that CEFTA'S impact on exports and economic growth and development of its members is positive while others claim that this impact is either very limited or no existent at all. The current research aims to assess CEFTA's impact on growth and development taking into consideration the domestic economic and political environment. In addition, it extends recent work assessing CEFTA's effectiveness on member-states focusing on trade, economic growth and development by taking into consideration additional macroeconomic variables as well as the domestic capabilities of each member.
Keywords: F15; F50; F63; 330; International Economic Relation; Regional Trade Agreements; Free Trade Agreements; CEFTA